Executive functioning and central coherence in anorexia nervosa: Pilot investigation of a neurocognitive endophenotype. (27th April 2018) - Brown, Melanie; Loeb, Katharine L.; McGrath, Robert E.; Tiersky, Lana; Zucker, Nancy; Carlin, Amanda
Abstract: A neurocognitive profile characterized by problems in set shifting, executive functioning, and central coherence may pre‐date and maintain anorexia nervosa (AN). To test this pattern as a possible endophenotype for AN, 10 youth with current AN, 14 healthy youth, and their biological parents, participated in a neuropsychological battery. Youth with AN demonstrated significantly weaker central coherence, related to enhanced detail‐focused processing. Youth with AN and their parents demonstrated significantly greater psychopathology relative to controls, and youth–parent scores were significantly correlated. The study, limited by a small sample size, found little evidence supporting a neuropsychological endophenotype for AN. Identifying a neurocognitive profile for children and adolescents with AN has important implications for the treatment of young patients.